x(2x+3)=4

Simple and best practice solution for x(2x+3)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2x+3)=4 equation:


Simplifying
x(2x + 3) = 4

Reorder the terms:
x(3 + 2x) = 4
(3 * x + 2x * x) = 4
(3x + 2x2) = 4

Solving
3x + 2x2 = 4

Solving for variable 'x'.

Reorder the terms:
-4 + 3x + 2x2 = 4 + -4

Combine like terms: 4 + -4 = 0
-4 + 3x + 2x2 = 0

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
-2 + 1.5x + x2 = 0

Move the constant term to the right:

Add '2' to each side of the equation.
-2 + 1.5x + 2 + x2 = 0 + 2

Reorder the terms:
-2 + 2 + 1.5x + x2 = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 1.5x + x2 = 0 + 2
1.5x + x2 = 0 + 2

Combine like terms: 0 + 2 = 2
1.5x + x2 = 2

The x term is 1.5x.  Take half its coefficient (0.75).
Square it (0.5625) and add it to both sides.

Add '0.5625' to each side of the equation.
1.5x + 0.5625 + x2 = 2 + 0.5625

Reorder the terms:
0.5625 + 1.5x + x2 = 2 + 0.5625

Combine like terms: 2 + 0.5625 = 2.5625
0.5625 + 1.5x + x2 = 2.5625

Factor a perfect square on the left side:
(x + 0.75)(x + 0.75) = 2.5625

Calculate the square root of the right side: 1.600781059

Break this problem into two subproblems by setting 
(x + 0.75) equal to 1.600781059 and -1.600781059.

Subproblem 1

x + 0.75 = 1.600781059 Simplifying x + 0.75 = 1.600781059 Reorder the terms: 0.75 + x = 1.600781059 Solving 0.75 + x = 1.600781059 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.75' to each side of the equation. 0.75 + -0.75 + x = 1.600781059 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + x = 1.600781059 + -0.75 x = 1.600781059 + -0.75 Combine like terms: 1.600781059 + -0.75 = 0.850781059 x = 0.850781059 Simplifying x = 0.850781059

Subproblem 2

x + 0.75 = -1.600781059 Simplifying x + 0.75 = -1.600781059 Reorder the terms: 0.75 + x = -1.600781059 Solving 0.75 + x = -1.600781059 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.75' to each side of the equation. 0.75 + -0.75 + x = -1.600781059 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + x = -1.600781059 + -0.75 x = -1.600781059 + -0.75 Combine like terms: -1.600781059 + -0.75 = -2.350781059 x = -2.350781059 Simplifying x = -2.350781059

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.850781059, -2.350781059}

See similar equations:

| 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 | | 5x-11=4x+6 | | 4w-6w=12 | | 9x-15=6x |

Equations solver categories